Peran Rukun Keluarga dalam Tradisi Kumawus Masyarakat Kelurahan Walian Kecamatan Tomohon Selatan - Yohanes Burdam; Eka Yuliana Rahman; Aksilas Dasfordate (Universitas Negeri Padang, 2022)
Abstract (Bahasa Inggris) This article is explain and analyze form of contribution of family pillars in the implementation of the kumawus tradition and identify and analyze the factors that underlie the involvement of the family pillars in the implementation of the kumawus tradition in the grieving family of the Walian village community in South Tomohon sub-district, Tomohon city. used a qualitative descriptive approach (qualitative approach) while the data collection methods, namely: observation, interviews, documentation, and literature study. data analysis using Miles and Huberman interactive model analysis. From the results of the study, it can be seen that the role of family pillars is not only carried out when the kumawus tradition is carried out in grieving families. But the role of family pillars has been carried out at the time of a bereavement to one of the grieving family members. In the implementation of the kumawus tradition for grieving families, the role of harmony is carried out by women and men starting from preparing additional mourning tents, preparing materials that will be processed into food and drink ingredients, serving guests on Sundays when the kumawus tradition is carried out. The family pillars also provide financial assistance from the harmonious organization in addition to financial assistance from each family. Family pillars also provide moral reinforcement to families who are suffering from grief. All the roles of the family rukn are carried out on the basis of the philosophical foundation of